EFFECT OF AUDIO THERAPY USING AL-QUR'AN MURROTAL ON BEHAVIOR DEVELOPMENT IN CHILDREN WITH AUTISM - Anjar Astuti; Suryono Suryono; Melyana Nurul Widyawati; Ari Suwondo; Mardiyono Mardiyono (Belitung Nursing Journal, 2017)
Background: Autism is a neurodevelopmental disorder. Audio therapy is considered as one of the complementary therapies to improve the behavior of children with autism. Objective: This study was to analysis the effectiveness of the Al-Qur'an murrotal audio therapy on behavioral development in children with autism. Methods: This study was a true-experimental research using pretest and posttest approach with control group. This research was conducted on November 2016 in the Autism Foundation of Semarang City, Indonesia. There were 30 samples were selected using simple random sampling, with 15 samples assigned in the experiment and control group. Mann Whitney and Wilcoxon tests were used for data analysis in this study. Results: Results showed that there was a significant difference in the mean of behavioral development after given intervention between the experiment group and control group with p-value 0.034 (<0.05). The mean of behavioral development in the experiment group (4.53) was higher than the mean in the control group (3.47). Conclusion: The Al-Qur'an murrotal audio therapy is effective to develop behavior of children with autism. Therefore, it is expected that this audio therapy can be applied an alternative therapy for children with autism.